Stringing Together Diversity: Exploring Indonesian Culture Through The TRI N Integrated Indonesian Traditional House (Puradi) Puzzle (Niteni, Nirokke, Nambahi) - Pri Hastuti Komarul; Insanul Qisti Bariyah; Heri Maria Zulfiati; Sutrisna Wibawa (Eduvest - Journal of Universal Studies, 2025)
This study aims to explore the effectiveness of the project "Stringing Together Diversity: Exploring Indonesian Culture Through the Tri N Integrated Indonesian Traditional House (PURADI) Puzzle" in improving the understanding of phase B students about cultural diversity in Indonesia. The research background is based on the importance of introducing and instilling diversity values from an early age, as well as utilizing an interactive and fun learning approach. This research uses a research and development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The subject of the study is a phase B student at SD Negeri Gembongan. Data was collected through participant observation, semi-structured interviews with students and teachers, and document analysis in the form of puzzle work. The results of the study show that the PURADI project is effective in increasing students' knowledge about various traditional houses in Indonesia, as well as developing their ability to identify cultural differences. In addition, the integration of Tri N values (Niteni, Nirokke, Nambahi) in this project is able to encourage students to observe, imitate, and develop their understanding of culture in a more in-depth way. The conclusion of this study is that the PURADI project is an innovative and effective learning method in instilling an understanding of Indonesian cultural diversity in elementary school students